UPAYA MENINGKATKAN HASIL BELAJAR TEMA 6 DENGAN MODEL DISCOVERY LEARNING PADA SISWA KELAS IV SD NEGERI CEBONGAN 02 SALATIGA - Riski Setiani; Henny Dewi Koeswanti; Elvira Hoesein Radia (JURNAL TEMATIK, 2019)
This study aims to improve the learning outcomes of theme 6 with a model of discovery  learning  in  fourth  grade  students  of  Cebongan  02  Elementary  School  in Salatiga. This research method uses classroom action research which follows the models of Kemmis and Taggart. This study includes 4 stages, namely planning (planning), implementation (acting), observation (observing), and reflection (reflecting). The results showed that the learning outcomes obtained from the results of the first semester middle test consisting of theme 1 and some in theme 2 were less satisfactory at pre-cycle, KKM was 75. Of the 22 students completeness only reached 31.81% or as many as 7 students, while students who did not complete reached 68.18% or 15 students with an average value of 66.5 especially the IPA content. and experienced improvement in the first cycle with a percentage of 63.7% and increased again in the second cycle of 90.9% according to the indicator of success. This study concludes that the Discovery learnig learning model can improve learning outcomes in theme 6 subjects, especially science subjects.